Neskončnost povojne rekonstrukcije - Bartulović, Alenka (Etnolog. Nova vrsta (Ljubljana), 2012)
Post-war rehabilitation of society in Bosnia and Herzegovina, based on the principle of exalting exclusivist affiliation with one of the three constituent nations, has been rather unsuccessful and has led to anger and disappointment in Sarajevo; however, besides despair it has also produced hopes for a better future. The main target of the criticism from the people ofSarajevo is the failure to establish a Žnormal lifeŽ within the framework ofa dysfunctional Žnon-existing stateŽ. The article describes how individuals,who declare themselves to be anti-nationalists and Bosnians or Herzegovinians, practice hope in post-war Sarajevo and offers insight into thespecific, often quite contradictory practices that reflect people's longingfor a different Bosnian-Herzegovinian future.
Keywords: ethnology; etnologija; hope; ljudsko življenje; upanje; waiting; Yugonostalgia; Yugo-nostalgia; jugonostalgija; antinacionalizem; anti-nationalism; Sarajevo; Bosnia and Herzegovina; Bosna in Hercegovina